Exploring adolescent mental health during the COVID-19 crisis – strengths and difficulties - Loy, Johanna K.; Klam, Janina; Dötsch, Jörg; Frank, Julia; Bender, Stephan (Frontiers in Public Health, 2024)
The SARS-CoV-2 pandemic has significantly impacted children and adolescents, leading to mental health challenges. Knowledge on their resources and difficulties is crucial and there is a need for valid instruments to assess their psychosocial condition in this exceptional situation. We assessed psychopathological symptoms using the SDQ during the pandemic, comparing to pre-pandemic data. Our study aims to understand adolescents' strengths and difficulties amidst COVID-19, evaluating the SDQ's utility in crisis settings. Within the German school-based surveillance study ("B-Fast"), we assessed behavioral strengths and difficulties in 664 adolescents aged 11-17 years during the peak of the German COVID-19 pandemic using the validated Strength and Difficulties Questionnaire (SDQ) for both external and self-assessed data collection. Data were collected between November 2020 and April 2021. We compared self-assessed SDQ-scores to pre-pandemic data from a comparable sample and examined adolescent classification as “normal” or “borderline/abnormal” using established cut-off values. Additionally, we conducted sex and rater-based score comparisons. We observed a significant worsening of "Emotional Symptoms" compared to pre-pandemic levels, while "Conduct Problems" and "Prosocial Behavior" showed improvement. Variations in classification to "normal" and "abnormal" emerged when applying German versus British cut-off values. Females scored higher on "Emotional Symptoms" while males scored higher on "Hyperactivity Symptoms." Correlations between external and self-assessed SDQ ratings ranged from 0.43 (p<0.001) for “Prosocial Behavior” among girls to 0.62 (p<0.001) for “Peer Problems” among boys, indicating moderate to high consistency. Our study contributes to understanding the psychosocial impact of the COVID-19 pandemic on German adolescents. Compared to other symptoms, we observed a particular worsening in "Emotional Symptoms" based on our data. Despite the moderate correlation between parental and self-reported evaluations, there appears to be a certain discrepancy in the perception of adolescent quality of life. Therefore, it seems prudent to assess both the external and self-reported evaluations and amalgamate the results from both parties to obtain a comprehensive problem profile of the individual. These findings underscore the importance of using country-specific cutoff values and reaffirm the utility of the SDQ as a valuable assessment tool, even within the unique circumstances posed by a pandemic.